2004
DOI: 10.1002/jqs.823
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary deglaciation and climate history of the Larsemann Hills (East Antarctica)

Abstract: The Late Quaternary climate history of the Larsemann Hills has been reconstructed using siliceous microfossils (diatoms, chrysophytes and silicoflagellates) in sediment cores extracted from three isolation lakes. Results show that the western peninsula, Stornes, and offshore islands were ice-covered between 30 000 yr BP and 13 500 cal. yr BP. From 13 500 cal. yr BP (shortly after the Antarctic Cold Reversal) the coastal lakes of the Larsemann Hills were deglaciated and biogenic sedimentation commenced. Between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 75 publications
(98 reference statements)
2
49
0
Order By: Relevance
“…A previous study has also revealed that the Schirmacher Oasis was probably deglaciated at the Pleistocene-Holocene boundary (Gingele et al 1997). This phenomenon is almost similar to that in the Larsemann Hills where the lakes were ice-free during 11.5 and 9.5 ka BP (Verleyen et al 2003(Verleyen et al , 2004a(Verleyen et al , 2004bHodgson et al 2004). This rise in temperature can be correlated with the commencement of the Holocene warming in other East Antarctic oases (Ingόlfsson et al 1998;Gore et al 2001;Hodgson et al 2001;Kirkup et al 2002).…”
Section: Discussionsupporting
confidence: 78%
“…A previous study has also revealed that the Schirmacher Oasis was probably deglaciated at the Pleistocene-Holocene boundary (Gingele et al 1997). This phenomenon is almost similar to that in the Larsemann Hills where the lakes were ice-free during 11.5 and 9.5 ka BP (Verleyen et al 2003(Verleyen et al , 2004a(Verleyen et al , 2004bHodgson et al 2004). This rise in temperature can be correlated with the commencement of the Holocene warming in other East Antarctic oases (Ingόlfsson et al 1998;Gore et al 2001;Hodgson et al 2001;Kirkup et al 2002).…”
Section: Discussionsupporting
confidence: 78%
“…Earlier studies focusing on environmental aspects of this region were carried out by Gillieson (1991), Hodgsn et al (2005), Verleyen et al (2004) and many other scientists. This presentation will highlight the different hydro-chemical aspects.…”
Section: Objective Of the Workmentioning
confidence: 98%
“…ka B.P. as suggested by the low lake levels (Verleyen et al, 2004). Lakes in the Bunger Hills were also covered by ice for an extended period, indicating cold and dry conditions with reduced melt-water input from 9 to 5.5 cal.…”
Section: Interpretation Of the Magnetic Data For Sandy Lake Sediment mentioning
confidence: 99%